Renal injury, biomarkers, and myositis, an understudied aspect of disease: prospective study in the MyoCite cohort - Conticini, Edoardo; Naveen, R.; Sen, Parikshit; Singh, Mantabya; Rathore, Upendra; Anuja, Anamika Kumari; Rai, Mohit Kumar; Yadav, Brijesh; Prasad, Narayan; Agarwal, Vikas; Gupta, Latika (Frontiers in Medicine, 2023)
Introduction: The mechanisms leading to chronic renal injury in patients with idiopathic inflammatory myopathies (IIMs) are poorly understood. Weassessed the prevalence of subclinical renal injury in patients with IIMs, through elevation in biomarker levels of tubular injury and fibrosis (NGAL, KIM1, Activin A, CD163, and Cys-c), and assesseddifferences between subtypesof IIMs, and the effect of disease activity and duration Materials and methods: Clinical data, core set measures (HAQ-DI, patient and physician global assessment, , MMT8, MDI, MDAAT, muscle enzymes), sera and urine were prospectively collected from all patients enrolled in the MyoCite cohort from 2017 to 2021. Twenty healthy subjects (HC) and 16 patients withacute kidney injury (AKI) were included as controls.Baseline and Follow up data for IIMs were included.Enzyme-linked immunosorbent assay (ELISA) was used to measure urine NGAL(Human Lipocalin-2/NGAL Duoset ELISA, Cat no: DY1757), KIM1(Human TIM-1/KIM 1/HAVCR Duoset ELISA, Cat.no: DY1750B), Activin A(Human Activin A Duoset ELISA, Cat no: DY338), CD163(Human CD163 Duoset ELISA ,Cat no: DY1607-05), and Cys-c (Human Cystatin C Duoset ELISA, Cat. no.: DY1196) levels, while eGFR (unit ml/min/1.73m2) was calculated by the Cockcroft-Gault formula and CKD-EPI formula. Results: Analysis of 201 visits of 110 adult patients with IIMsindicated higher normalized biomarker levels compared to HCs, and comparable to patients with AKI, with the exception of NGAL, which was higher in the AKI group. Notably 72 (49%) patients withIIMs had eGFR<90; the levels of the 5 biomarkers were comparable between active and inactive IIMs, and different subtypes of IIMs.Similarly, a poor correlation between urine biomarker levels andcore set measures ofactivity and damage was found. Changesin biomarker levels on follow-up did not correlate with eGFR changes. Discussion: This exploratory analysis of urinary biomarkersidentified low eGFR and elevated biomarkers of chronic renal injury in nearly half of the patients with IIMs, comparable to patients with AKI and higher than HCs, indicative of potential renal damage in IIMs that may have a lead to complications inother systems